Leadership Strategies in the Management of Pesantren Darussalam Blokagung Banyuwangi in the Digital Era - Huzali, Ikhsan; Aimah, Siti; Sidique, Shaufique Fahmi Ahmad (Electronic Journal of Education, Social Economics and Technology, 2025)
This research explores leadership strategies in Islamic boarding school education management in the digital era, with a focus on the Darussalam Blokagung Islamic Boarding School. Researchers use Everett Rogers' (1962) Innovation Adoption theory. Because the theory is comprehensive and relevant for understanding the implementation of technology in Islamic boarding schools in the digital era. By understanding this theory, Islamic boarding school leaders can develop effective strategies for implementing technology and improving the quality of learning in Islamic boarding schools. A qualitative case study approach was used to understand the unique Islamic boarding school context and its challenges in integrating technology. Research findings show that the implementation of technology in Islamic boarding school education presents challenges and opportunities. The main challenges are the lack of adequate technological infrastructure, high implementation costs, and socio-cultural impacts. However, technology also offers opportunities to improve the quality of learning, such as developing relevant curricula, implementing learning methods that utilize technology, increasing student engagement, and preparing students to face global demands. Effective leadership strategies in managing Islamic boarding school education in the digital era include the use of technology, building a culture of collaboration between staff, students and parents, as well as evaluating and monitoring the progress of technology implementation. Implementing these strategies can help Islamic boarding schools to improve the quality of education, prepare students for the future, and preserve the Islamic values and identity of Islamic boarding schools in the digital era.